Computational electromagnetic analysis of partially-filled rectangular waveguide at X-band frequencies - Zamaraite, Ilona; Rudys, Saulius; Lapinskas, Saulius; Aleksiejunas, Rimvydas; Grigalaitis, Robertas; Banys, Juras (Nonlinear Analysis: Modelling and Control, 2022)
In this paper, the full-wave analysis of the direct scattering problem in the rectangular waveguide is derived. The numerical calculation results of the scattering characteristics are presented. To show the advantage of our proposed model, we compared direct problem results with three-dimensional simulation software Ansys HFSS calculations. An excellent agreement is observed when compared these two approaches.